ESF funded training for unemployed women: policy aims and implementation - Brine, Jacky (1993)
The European Social Fund (ESF) provides funding for vocational training projects for unemployed women aged over 25. This research traces the development of ESF policies and interpretations from within the European Commission and the British government from 1958 to 1993. The position of women within the European and British labour markets provides the basis of the evaluation of the ESF's aim to increase employability through training linked to the needs of the labour market.